2020
DOI: 10.1002/term.3027
|View full text |Cite
|
Sign up to set email alerts
|

In vivo tissue engineering of an adipose tissue flap using fat grafts and Adipogel

Abstract: For decades, plastic surgeons have spent considerable effort exploring anatomical regions for free flap design. More recently, tissue-engineering approaches have been utilised in an attempt to grow transplantable tissue flaps in vivo. The aim of this study was to engineer a fat flap with a vascular pedicle by combining autologous fat grafts and a novel acellular hydrogel (Adipogel) in an established tissue-engineering model

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…We have deliberately not chosen other vascularized control groups in our study as our key interest was to evaluate mSVF proliferation over time and not its superiority to other cell sources or SVF isolation protocols. Beyond that, previous well-conducted studies already showed that minced fat [25] or enzymatically isolated ASCs [26] promoted angiogenesis and tissue growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have deliberately not chosen other vascularized control groups in our study as our key interest was to evaluate mSVF proliferation over time and not its superiority to other cell sources or SVF isolation protocols. Beyond that, previous well-conducted studies already showed that minced fat [25] or enzymatically isolated ASCs [26] promoted angiogenesis and tissue growth.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the only work that has scrutinized mechanically manipulated fat tissue by an arteriovenous loop was recently published by the group around Wayne Morrison [25], who crudely minced and centrifuged adipose tissue instead of disrupting adipocytes. Similar to our observations, Debels et al also found an increase in weight and perilipin expression of the implanted fat tissue over time.…”
Section: Discussionmentioning
confidence: 99%
“…An additional manipulation of the method was introduced by Debels et al, 28 TECs with vessel loops, fat grafts, and acellular hydrogel (Adipogel). Although adipocyte and ASC death was noted in early stages, by 12 weeks, the tissue contained live adipocytes, which were not survivors of the original graft, but newly formed cells.…”
Section: Tissue Engineering Chambermentioning
confidence: 99%
“…Debels et al have compared processed fat alone with a composite material consisting of an adipose-derived acellular matrix enriched with fat as a scaffold for arteriovenous loop–based tissue engineering and demonstrated that the combination of an acellular scaffold with viable fat significantly enhances the regenerative process. 35 Fractionated fat has been shown to improve wound healing in diabetic rats and photoaging in nude mice, indicating its merit for regenerative medicine. 25,26 Huang et al used nanofat in conjunction with ceramic granules to promote chondrogenic differentiation of mesenchymal progenitor cells, further highlighting the potential of nanofat/fractionated fat for bone tissue engineering.…”
Section: Discussionmentioning
confidence: 99%